Ten new species of Sticta and counting: Colombia as a hot spot for unrecognized diversification in a conspicuous macrolichen genus - Moncada, Bibiana; Lücking, Robert (Phytotaxa, 2012)
As part of a systematic and taxonomic revision including molecular phylogenetic analysis, ten new species of the lichen genus Sticta are described from Colombia, some of them also being reported from Guatemala, Venezuela, Ecuador, Bolivia, and Chile: Sticta arachnofuliginosa Moncada & Lücking, sp. nov., S. arbuscula Moncada & Lücking, sp. nov., S. isidiokunthii Moncada & Lücking, sp. nov., S. maculofuliginosa Moncada & Lücking, sp. nov., S. microcyphellata Moncada & Lücking, sp. nov., S. papillata Moncada & Lücking, sp. nov., S. rhizinata Moncada & Lücking, sp. nov., S. rubropruinosa Moncada & Lücking, sp. nov., S. silverstonii Moncada & Lücking, sp. nov., and S. tunjensis Moncada & Lücking, sp. nov. The new species represent the major morphological groups within the genus, including taxa with green or blue-green photobiont and with predominantly sexual (apothecia) or vegetative (isidia) reproduction. Detailed morphological, anatomical, and chemical descriptions are given for each species, and all taxa are briefly discussed. We also introduce several novel characters useful in the taxonomy of Sticta.